PENINGKATAN HLASIL BELAJAR MATEMATIKA MATERI PENGURANGAN MENGGUNAKAN MEDIA PAPAN BERHLITUNG PADA PESERTA DIDIK KELAS I SD NEGERI SAWAHL BESAR 01 - Afika Muzayyanahl; Mira Azizahl; Kartinahl (STKIP Subang, 2023)
The purpose of this study was to improve the learning outcomes of subtraction material by using a counting board for first grade students at SDN Sawah Besar 01 consisting of 29 students. This type of research is class action assessment using the spiral model which is carried out in two cycles. The data collection techniques used were observation, test or evaluation, and documentation, then a descriptive analysis was carried out from the data obtained. The results showed that after giving action for two cycles the average value of the learning outcomes assessment test with arithmetic reduction using a counting board in mathematics subject experienced an increase in the first cycle resulting in a percentage value of 59% and an average of 75.17, while for the second cycle the increase percentage of 31% to 90% with an average of 93.10. It can be concluded that the counting board media can be further applied to improve student learning achievement, especially in mathematics subject matter of addition.